Oil in the environment : legacies and lessons of the Exxon Valdez oil spill - Wiens, John A. (Cambridge University Press, 2013)
Scientists directly involved in studying the Exxon Valdez spill provide a comprehensive synthesis of scientific information on long-term spill effects.